Uma teoria ovidiana da literatura: os Tristia como epitáfio de um poeta-leitor - Júlia Batista Castilho de Avellar (2019)
The present work points out possibilities of interaction between the Classical Studies and the Theory, and investigates the meta-literary nature of Ovid’s poetry, especially in his first collection of exile elegies, the ‘Tristia’ (‘Sadnesses’, I AD), when the Latin writer reflects on and theorizes about the status of a poetic text, its production and reception. At the end of the thesis, I present my translation of the ‘Tristia’ five books to Portuguese. By analyzing these questions and the ideas of poetic genre, intertextuality and reception, I propose an approach to the works of Antiquity which, combining philology and theory, can discuss theoretical-literary concepts in the specificities of the Classical Studies. For this, I created the notion of ‘intertextual philology of reception’ as a possible means of approaching the classical works in the contemporary world, in order to highlight the significance of Antiquity today and its connections to and dialogues with the current context. The analysis were based on the dialogue of the ‘Tristia’ with the poet’s previous productions, in order to provide an overall view of the Ovidian Work, and to show its principle of continuity, in opposition to the generally widespread idea of rupture due to exile. The resumption of Ovidian previous works in the exile elegies is here understood as an (auto)reception process, in which Ovid becomes a reader of his own works, and also of the literary tradition. This process occurs in two main ways: first, the poet’s works are mentioned with critical and meta-poetic commentaries, and the first-person speaker Naso evaluates his earlier writings and reinterprets them; second, Ovid re-employs and reframes various compositional procedures previously used in his earlier works, so that the ‘Tristia’ become a kind of rewriting of previous productions. Thus, they are a synthesis of Ovidian precedent production, like an epitaph to the poet who metaphorically died with exile; they record Naso’s poetic trajectory and literary autobiography. By creating a ‘myth’ of Ovid’s life and exile, the ‘Tristia’ form a kind of reflective literature, which, in literary doing, theorizes about itself; a kind of ‘Ovidian Literary Theory’, based on erotic and metamorphic dialogue. This way, the Ovidian exile becomes also, in the metaphorical sense, the virtual space of poetic activity, that is, an exile of the writer during the creation process.